Pengaruh Likuiditas, Leverage, dan Ukuran Perusahaan Terhadap Profitabilitas pada Perusahaan Tekstil dan Garmen yang Terdaftar di BEI Periode 2019-2022 - Bella Nutia Febriana; Dwi Wahyuningsih (MES Management Journal, 2024)
The “purpose of this study is to identify the relationship between profitability and the variables of liquidity, leverage, and firm size. Information for this study came from textile and garment businesses that were listed on the Indonesia Stock Exchange between 2019 and 2022. The purposive sampling technique was used to do the sampling. The following tests are employed for data analysis: Multiple Regression Analysis, Hypothesis Testing, Descriptive Statistics, and Classical Assumption Test. This study's findings demonstrate that ROA is significantly impacted by liquidity (CR), leverage (DER), and firm size (LnTA) all at once. Profitability (ROA) is positively impacted by liquidity (CR) and leverage (DER) in textile and garment firms listed on the Indonesia Stock Exchange (BEI) in 2019-2020, while company size (LnTA) has no effect on” ROA. Keywords: Profitability, Liquidity, Leverage, and Company Size